Hedera nepalensis K. Koch: A Novel Source of Natural Cancer Chemopreventive and Anticancerous Compounds. (21st December 2015) - Jafri, Laila; Saleem, Samreen; Kondrytuk, Tamara P.; Haq, Ihsan‐ul; Ullah, Nazif; Pezzuto, John M.; Mirza, Bushra
Abstract : Traditional medicinal plants are often used for both the prevention and the treatment of local diseases. Taking into consideration the medicinal importance of Hedera nepalensis within local Pakistani traditions, the present study was undertaken to analyze the in vitro cancer chemopreventive and cytotoxic properties of the plant. The in vitro cancer chemopreventive testing was performed using nitrite assay, NFκB assay, aromatase assay, and quinone reductase 1 (QR1) assay. The cytotoxic potential was evaluated on three cancer‐cell lines: MCF‐7, MDA‐MB‐231, and HeLa using sulforhodamine B (SRB) assay. The results of cancer chemopreventive assays show that n‐ hexane and ethyl acetate fractions of tested plant have promising cancer chemopreventive potential. Lupeol isolated from n ‐hexane as well as ethyl acetate fraction showed lowest IC50 (0.20 ± 1.9 μM) in NFκB assay. Crude extract and its fractions inhibited the growth of three cancer cell lines by more than 60%, IC50 value of lupeol varied from 2.32 to 10.2 μM. HPLC‐DAD‐based quantification of lupeol in different plant tissues demonstrated that leaves of H. nepalensis are a rich source of lupeol (0.196 mg/100 mg dry weight). Our data have shown that H. nepalensis harbors cancer chemopreventive and cytotoxic agents. Copyright © 2015 John Wiley & Sons, Ltd.